Antiviral drugs from the nucleoside analog family block volume-activated chloride channels. - Gschwentner, M. (The Feinstein Institute for Medical Research, 1995)
BACKGROUND: The antiviral drugs AZT and acyclovir are generally used in the treatment of infections with human immunodeficiency virus (HIV) and herpes simplex virus (HSV). These substances are known to impede virus replication by premature nucleic acid chain termination. It is not yet clear, however, if this is the sole mechanism responsible for the antiviral and/or the numerous side effects observed in patients treated with these agents. We investigated the swelling-induced chloride current in fibroblasts, which we demonstrated is closely related or identical to a cloned epithelial chloride channel, ICln: This chloride channel can be blocked by nucleotides. MATERIALS AND METHODS: Electrophysiological, fluorescence optical, and volume measurements were made to determine the effect of nucleoside analogs on the swelling-dependent chloride current (ICl) in NIH 3T3 fibroblasts and in human T cell lymphoma (H9) cells and the cAMP-dependent chloride current in CaCo cells. RESULTS: AZT and acyclovir block the swelling-dependent chloride current and the chloride flux in fibroblasts, and the regulatory volume decrease (RVD) and ICl in H9 cells. This immediate effect can be substantially reduced by the simultaneous incubation of the cells with thymidine-5'-diphosphate (TDP) or uridine, both of which are by themselves unable to affect ICl. CONCLUSIONS: We show here a novel molecular mechanism by which antiviral drugs of the nucleoside analog family could lead to impairments of the kidney, bone marrow, gastrointestinal, and neuronal functions, and how these side effects could possibly be restricted by the presence of TDP or uridine.